Radiographic Assessment of Root/Crown Ratio and Short Root Anomaly: A Retrospective Study in Chinese Population - Ye, Yuer; Pan, Yiqi; Zhang, Hui; Chen, Yani; Yang, Guoli; Jiang, Zhiwei; Wang, Ying (Orthodontics & craniofacial research, 2025)
ABSTRACT Objectives Research suggested that racial and gender differences may exist in tooth root development and the prevalence of short root anomaly (SRA). However, data on Asian and specifically Chinese populations were limited. This retrospective study aimed to evaluate the prevalence of SRA and the characteristics of the root‐to‐crown ratio (R/C ratio) within the Chinese population. Materials and Methods Modified Lind's criteria were used to measure the crown and root lengths in permanent dentition. A total of 27 142 teeth from 1000 subjects were evaluated using panoramic radiographs. Fisher's exact test was employed to analyse gender differences in SRA. Paired‐sample and independent‐sample t tests were used to assess the characteristics of R/C ratios. Results SRA was observed in 27 patients, with a prevalence of 2.7% and a tooth prevalence of 0.309%. Females had a significantly higher prevalence of SRA compared to males (p < 0.01). SRA was found exclusively in incisors (83.72%) and premolars (16.28%), with the maxillary central incisor being the most commonly affected tooth. Additionally, there were statistical differences in the R/C ratio based on gender and jaw position in the normal groups. The highest R/C ratios were observed in the mandibular second premolars, while the maxillary central incisors had the lowest ratios. Conclusions SRA was relatively common in the Chinese population, and clinicians should be aware of its presence. It was more frequently observed in females and shows specificity in tooth position, with the maxillary central incisor being the most commonly affected tooth. Our study provides valuable insights for the early diagnosis and treatment of SRA in the Chinese population.